The Effect of Hatay Mustafa Kemal University Academic Staff's Workplace Leisure Preferences on Health Perceptions - SÜNER, Akay; AKTAŞ ÜSTÜN, Neslişah (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2022)
This study aimed to examine the effects of workplace leisure preference on the health perception of Hatay Mustafa Kemal University academic staff. The research was designed as correlational cross sectional quantitative study and 400 randomly chosen faculty members working in faculties and colleges in Tayfur Ata Sökmen Campus participated in the study. In the research, data were collected with personal information form, Work Place Leisure Preferences Scale and Health Perception Scale. SPSS 23 package program for Windows was used to evaluate the data. Missing value analysis was applied to the data and one data was excluded from the study. Internal consistency coefficients and mean, standard deviation, kurtosis and skewness values for the calculated scales were examined. Pearson Correlation analysis and Multiple Liner Regression test were used as hypothesis tests. In conclusion, this study showed that there was a significant relationship between participants' work place leisure preferences and their health perceptions, and work place leisure preference is a predictor of health perception.